Perbedaan Efisiensi Perusahaan Asuransi Jiwa Syariah dan Konvensional di Indonesia Dengan Metode Data Envelopment Analysis (DEA) - Yurike Fitria Astuti; Noven Suprayogi (Jurnal Ekonomi Syariah Teori dan Terapan, 2017)
This study aims to determine and comparing the level of operational efficiency of Islamic Life Insurance and Conventional Life Insurance in Indonesia. This study uses a quantitative non-parametric approach With Data Envelopment Analysis (DEA) CRS and VRS assumption, and a statistical tool Mann-Whitney U-Test. The samples are 13 Islamic Insurance and 5 Conventional Insurance that comply with the specified sample criteria. During 2010 to 2014, the relative average value of Islamic Life Insurance and Conventional Life Insurance with VRS assumption more efficient than CRS assumption. This indicates that in relative terms, the source of operational inefficiency is not effective on the efficiency scale. While the hypothesis test results showed no significant differences in levels of operational efficiency in both groups the data by CRS assumptions and VRS.